THE PRINCIPLE OF ISLAH IN THE MEDIATION OF DOMESTIC DISPUTES: A COMPARATIVE STUDY OF MEDIATION IN RELIGIOUS COURTS AND DISTRICT COURTS - Novia Nurul Izzati; Ahmad Sanusi; Itang Itang (Universitas KH. Abdul Chalim Mojokerto, 2026)
This article discusses how the principle of islah is applied in domestic dispute mediation, comparing the practice of the Religious Court and the District Court. This study aims to analyze Islamic law's perspective on the concept of islah and how it is applied in mediation in both courts. The method used in this study is normative legal research, with an approach encompassing legislation, conceptual analysis, and comparative analysis. The results show that mediation in the Religious Court, both normatively and practically, applies the principle of islah, focusing on peace, welfare, and restoration of family relationships, using a religious and persuasive approach. Meanwhile, although the term islah is not explicitly mentioned in mediation in the District Court, the values ​​of peace and justice are still implemented indirectly through mediation mechanisms based on positive law. This study concludes that the principle of islah is highly relevant for enriching the practice of domestic dispute mediation in Indonesia and can serve as a bridge to harmonize Islamic law and positive law.